Oligomer, composition, packaging structure, and method for disassembling packaging structure
By using an oligo formed by reacting bisacrylic monomer with epoxy resin or glycidyl methacrylate, combined with a second oligo reacting a compound containing an acrylic group and a liquid aromatic epoxy resin, a laser-decomposed frame glue composition is formed, which solves the problem that the frame glue cannot be disassembled after curing in the prior art, and realizes the decomposition of the frame glue and compatibility with liquid crystal displays.
Patent Information
- Application Number
- CN202111340124.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-10-14
- Filing Date
- 2021-11-12
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2041-11-12
AI Technical Summary
In existing liquid crystal displays, the frame glue material cannot be disassembled after curing, making it difficult to separate the substrate, affecting recycling and reprocessing.
An oligo formed by reacting a bisacrylic monomer with an epoxy resin or glycidyl methacrylate is used to form a laser-decomposed frame adhesive composition, combined with a second oligo reacting a compound containing an acrylic group and a liquid aromatic epoxy resin.
The decomposition of the frame glue is achieved. By irradiating the frame glue with laser, the frame glue expands in volume and breaks the molecular chain, which is conducive to the peeling of the glass substrate and avoids the impact on the liquid crystal display.
Smart Images

Figure CN115975152B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to oligomers, compositions, packaging structures, and methods for disassembling packaging structures. Background Art
[0002] The current mainstream consumer electronic products use liquid crystal display technology, and the recycling sources mainly include defective products in the panel assembly process and electronic waste. Whether it is panel recycling or reprocessing of defective products, the first step is to completely separate the two glass substrates (such as CF substrate and TFT substrate) before subsequent processing. Since the current frame glue cannot be disassembled after curing, there is an urgent need for disassembled frame glue materials to solve the above problems. Summary of the invention
[0003] The present invention provides an oligomer, which is formed by reacting a bis-acid monomer with (a) an epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is: Where X is -O-, And R 1 Each is CH 3 or CF 3 .
[0004] The present disclosure provides a composition comprising: a first oligomer; a second oligomer formed by reacting an acrylic acid-containing compound with a liquid aromatic epoxy resin; a multi-acrylate compound; an initiator; and a hardener, wherein the first oligomer is formed by reacting a bis-acid monomer with (a) an epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is:
[0005] Where X is -O-, And R 1 Each is CH 3 or CF 3 .
[0006] The packaging structure provided by the embodiment of the present disclosure includes: an optoelectronic device; and a sealant surrounding the edge of the optoelectronic device, wherein the sealant is hardened from a composition, and the composition includes: a first oligomer; a second oligomer formed by reacting an acrylic acid-containing compound with a liquid aromatic epoxy resin; a multi-acrylate compound; an initiator; and a hardener, wherein the first oligomer is formed by reacting a bis-acid monomer with (a) an epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is: Where X is -O-, And R 1 Each is CH 3or CF 3 .
[0007] The present disclosure provides a method for disassembling a package structure, which comprises: providing a package structure, wherein the package structure comprises: an optoelectronic device; and a sealant surrounding the edge of the optoelectronic device; and irradiating the sealant with a laser to decompose the sealant to disassemble the package structure, wherein the sealant is hardened by a composition, and the composition comprises: a first oligomer; a second oligomer formed by reacting an acrylic acid-containing compound with a liquid aromatic epoxy resin; a multi-acrylate compound; an initiator; and a hardener, wherein the first oligomer is formed by reacting a bis-acid monomer with (a) an epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is:
[0008] Where X is -O-, And R 1 Each is CH 3 or CF 3 . DETAILED DESCRIPTION
[0009] In some embodiments of the present disclosure, oligomers, compositions, packaging structures, and methods for disassembling packaging structures are provided, which can solve the problem that the substrate in the liquid crystal display is difficult to remove due to the adhesion of the frame glue. In the composition for forming the frame glue of the present disclosure, the main chain segment of the oligomer contains an imide molecular structure that can receive laser energy in the 193nm to 355nm band. In some embodiments, an acrylic or epoxy molecular chain segment is introduced into the oligomer, and the molecular structure of the oligomer can quickly absorb the laser pulse energy, resulting in a rapid expansion of the volume of the frame glue, and / or accompanied by the breaking of the molecular chain of the resin part, which is conducive to the shedding of the glass substrate.
[0010] On the other hand, when the composition is used as a sealant material in the manufacturing process of a liquid crystal display, it has not yet been cured when it comes into contact with the liquid crystal. Generally, under this condition, the ion purity (e.g., the concentration of chloride ions) in the sealant material will have a great impact on the display quality of the panel. The sealant material disclosed in the present invention can avoid the above problem, and after the ultraviolet (UV) and thermal curing process, there is no dissolution in the liquid crystal.
[0011] The oligomer provided in the embodiments of the present disclosure is formed by reacting a bis-acid monomer with (a) an epoxy resin or (b) glycidyl methacrylate. The structure of the bis-acid monomer is: Where X is -O-, And R 1 Each is CH 3 or CF 3 .
[0012] In some embodiments, (a) epoxy resin includes (a1) liquid aromatic epoxy resin, which is liquid at room temperature (e.g., about 18° C. to 35° C.). For example, (a1) liquid aromatic epoxy resin includes bisphenol A epoxy resin, bisphenol F epoxy resin, or a combination thereof. The structure of bisphenol A epoxy resin is The structure of bisphenol F epoxy resin is In some embodiments, (a) epoxy resin further comprises (a2) liquid aliphatic epoxy resin, and the liquid aliphatic epoxy resin is liquid at room temperature (eg, about 18° C. to 35° C.). For example, (a2) liquid aliphatic epoxy resin comprises C 3-10 Alkanediol diglycidyl ether (such as hexanediol diglycidyl ether, its structure is as follows: ).
[0013] In some embodiments, (a) epoxy resin is (a1) liquid aromatic epoxy resin, and the molar ratio of the bis-acid monomer to the (a1) liquid aromatic epoxy resin is between 1:2 and 1:8 or between 1:2.5 and 1:5. If the amount of (a1) liquid aromatic epoxy resin is too low, the bis-acid monomer is not easy to form a uniform phase with the epoxy resin. If the amount of (a1) liquid aromatic epoxy resin is too high, the viscosity of the oligomer is too high and is not suitable for the frame glue material. In some embodiments, (a) epoxy resin is a combination of (a1) liquid aromatic epoxy resin and (a2) liquid aliphatic epoxy resin, the molar ratio of the bis-acid monomer to the (a1) liquid aromatic epoxy resin is between 1:2 and 1:8 or between 1:2.5 and 1:5, and the molar ratio of the bis-acid monomer to the (a2) liquid aliphatic epoxy resin is between 1:2 and 1:7 or between 1:3 and 1:6. If the amount of (a1) liquid aromatic epoxy resin is too low, the bis-acid monomer is not easy to form a uniform phase with the epoxy resin. If the amount of (a1) liquid aromatic epoxy resin is too high, the viscosity of the oligomer is too high and is not suitable for the frame glue material. If the amount of (a2) liquid aliphatic epoxy resin is too low, the bis-acid monomer is not easy to form a uniform phase with the epoxy resin in a short time. If the amount of (a2) liquid aliphatic epoxy resin is too high, the content of bis-acid monomer in the oligomer is too low, which is not conducive to the laser disassembly process.
[0014] In some embodiments, the oligomer is formed by reacting a bis-acid monomer with (b) glycidyl methacrylate, and the molar ratio of the bis-acid monomer to (b) glycidyl methacrylate is between 1:10 and 1:20 or between 1:15 and 1:18. If the amount of (b) glycidyl methacrylate is too low, the bis-acid monomer is not easy to form a uniform phase with the epoxy resin. If the amount of (b) glycidyl methacrylate is too high, the content of the bis-acid monomer in the oligomer is too low, which is not conducive to the laser disassembly process. The structure of glycidyl methacrylate is
[0015] In some embodiments, the weight average molecular weight of the oligomer is 300,000 to 800,000. If the weight average molecular weight of the oligomer is too small, the mechanical properties of the frame glue material after curing are poor. If the weight average molecular weight of the oligomer is too large, the oligomer is not easy to process. In some embodiments, both ends of the above oligomer are epoxy groups, which can be applied to epoxy binder resin (epoxybinder).
[0016] The present disclosure provides a composition comprising: a first oligomer; a second oligomer formed by reacting an acrylic acid-containing compound with a liquid aromatic epoxy resin; a multi-acrylate compound; an initiator; and a hardener. The first oligomer may be the oligomer described above, and its details are not repeated here.
[0017] In some embodiments, the composition viscosity may be between 250,000 cps and 400,000 cps.
[0018] In the second oligomer formed by the reaction of an acrylic acid-containing compound and a liquid aromatic epoxy resin, the acrylic acid-containing compound may be acrylic acid, and the liquid aromatic epoxy resin may be a bisphenol A epoxy resin or a bisphenol F epoxy resin. The molar ratio of the acrylic acid-containing compound to the liquid aromatic epoxy resin may be between 1:1.05 and 1:1.5 or between 1:1.05 and 1:1.33. If the amount of the liquid aromatic epoxy resin is too low, it is not easy to form an effective reaction with the first oligomer when the seal material is thermally cured. If the amount of the liquid aromatic epoxy resin is too high, the UV reaction conversion rate will be insufficient when the seal material is UV cured. In some embodiments, the weight average molecular weight of the second oligomer may be 100,000 to 500,000. If the weight average molecular weight of the second oligomer is too small, the mechanical properties of the seal material after curing are poor. If the weight average molecular weight of the second oligomer is too large, the oligomer is not easy to process. In some embodiments, the weight ratio of the first oligomer to the second oligomer is between 1:1 and 1:10 or between 1:1.5 and 1:6. If the amount of the second oligomer is too low, the UV reaction conversion rate will be insufficient when the sealant material is UV cured. If the amount of the second oligomer is too high, the sealant material is not conducive to the laser disassembly process.
[0019] In some embodiments, the multi-acrylate compound may be dipentaerythritol penta- / hexa-acrylate (DPHA), trimethylolpropane triacrylate (TMPTA), pentaerythritol tetraacrylate (PETTA), dipentaerythritol pentaacrylate (DPEPA), ethoxylated trimethylolpropanetriacrylate (SR454), pentaerythritol triacrylate (SR444), or a combination thereof. In some embodiments, the weight ratio of the first oligomer to the multi-acrylate compound may be between 1:0.05 and 1:0.5 or between 1:0.09 and 1:0.38. If the amount of the multi-acrylate compound is too low, the UV reaction conversion rate will be insufficient when the frame glue material is UV cured. If the amount of the multi-acrylate compound is too high, the mechanical properties of the sealant material after curing will be poor.
[0020] In some embodiments, the initiator may be a photoinitiator, a thermal initiator, or a combination thereof, which can generate free radicals to polymerize double bonds after exposure to light or heating. In some embodiments, the weight ratio of the first oligomer to the initiator may be between 1:0.01 and 1:0.4 or 1:0.06 and 1:0.15. If the amount of the initiator is too low, the UV or thermal reaction conversion rate will be insufficient when the frame glue material is UV or thermally cured. If the amount of the initiator is too high, the mechanical properties of the frame glue material after curing are poor.
[0021] In some embodiments, the hardener can further cross-link and harden the resin. For example, the hardener can be 2-phenyl imidazole (2PZ), diaminodiphenylsulfone (DDS), boron trifluoride-amine complex (BF3-MEA), dicyandiamide (DICY), or a combination thereof. In some embodiments, the weight ratio of the first oligomer to the hardener can be 1:0.03 to 1:0.18. If the amount of the hardener is too low, the curing reaction conversion rate will be insufficient when the frame glue material is thermally cured. If the amount of the hardener is too high, the storage stability of the frame glue material will be poor.
[0022] In some embodiments, the composition may be optionally added with other additives such as inorganic fillers, flame retardants, leveling agents, other suitable additives, or combinations thereof, depending on the desired properties.
[0023] The present disclosure provides a packaging structure, which includes: an optoelectronic device; and a frame glue, surrounding the edge of the optoelectronic device, wherein the frame glue is hardened by the above-mentioned composition. In some embodiments, the optoelectronic device includes a liquid crystal display, a quantum dot light emitting diode display, an organic light emitting diode display, or a solar cell. Since the oligomer main chain segment in the composition contains an imide molecular structure that can receive laser energy in the 193nm to 355nm band, the frame glue can be decomposed by irradiating a 355nm laser to disassemble the packaging structure. When the optoelectronic device is a liquid crystal display, the frame glue material disclosed in the present disclosure does not affect the liquid crystal composition, and there is no dissolution in the liquid crystal after the ultraviolet light and thermal curing process. It is worth noting that the composition disclosed in the present disclosure can be used not only as a frame glue for a liquid crystal display, but also as a frame glue for other displays (such as quantum dot light emitting diode displays, organic light emitting diode displays, or other suitable displays) or solar cells, because it has a high adhesion strength to the substrate and can be disassembled after irradiating the laser.
[0024] The present disclosure also provides a method for disassembling a package structure, comprising: providing the above-mentioned package structure; and irradiating the sealant with a laser to decompose the sealant and disassemble the package structure. In some embodiments, the wavelength of the laser is 355 nm, and the laser intensity can be 20 μJ / cm per Hz energy. 2 Up to 120μJ / cm 2 (External power: 50kHz). If the laser intensity is too low, the package structure cannot be effectively disassembled. If the laser intensity is too high, it may cause the ITO glass and TFT substrate to be burned, causing the ITO resistance value to increase, the metal conductor of the TFT substrate to be disconnected, and the substrate cannot be reused.
[0025] In order to make the above contents and other purposes, features, and advantages of the present disclosure more clearly understood, preferred embodiments are specifically described in detail below:
[0026] [Example]
[0027] Synthesis example 1-1
[0028] Take 2 moles of 4-aminobenzoic acid, 1 mole of bisphenol A dianhydride (BPADA), and a catalytic amount of isoquinoline, add the solvent γ-butyrolactone (GBL), heat to 200°C and react for 4 hours to form monomer ABP. The structure of monomer ABP is as follows:
[0029]
[0030] Synthesis example 1-2
[0031] Take 2 moles of 1,2,4-trimethylolpropane (TMA), 1 mole of 4,4'-oxydianiline (ODA), and a catalytic amount of isoquinoline, add the solvent GBL, heat to 200°C and react for 4 hours to form a monomer ODT. The structure of the monomer ODT is as follows:
[0032]
[0033] Synthesis Example 1-3
[0034] 2 moles of p-aminobenzoic acid, 1 mole of hexafluorodianhydride (4,4'-(Hexafluoroisopropylidene)diphthalic anhydride, 6FDA), and a catalytic amount of isoquinoline were added to the solvent GBL, heated to 200°C and reacted for 4 hours to form monomer A6F. The structure of monomer A6F is as follows:
[0035]
[0036] Synthesis Example 1-4
[0037] Take 2 moles of trimellitic anhydride (TMA), 1 mole of 2,2-bis[4-(4-aminophenoxy)phenyl]propane (2,2-Bis[4-(4-aminophenoxy)phenyl]propane, BAPP), and a catalytic amount of isoquinoline, add the solvent GBL, heat to 200°C and react for 4 hours to form a monomer BAT. The structure of the monomer BAT is as follows:
[0038]
[0039] Synthesis example 2-1
[0040] 15 parts by weight of monomer ABP (0.02 molar equivalent), 15 parts by weight of bisphenol F epoxy resin (0.09 molar equivalent), and 15 parts by weight of hexanediol diglycidyl ether (0.07 molar equivalent, 1,6-hexanediol diglycidylether, HDGE) were mixed, heated to 150° C. and reacted for 4 hours to form an ABP binder resin.
[0041] Synthesis example 2-2
[0042] 15 parts by weight of monomer ODT (0.03 molar equivalent), 15 parts by weight of bisphenol F epoxy resin (0.09 molar equivalent), and 30 parts by weight of HDGE (0.13 molar equivalent) were mixed, heated to 150° C. and reacted for 2 hours to form an ODT binder resin.
[0043] Synthesis example 2-3
[0044] 15 parts by weight of monomer A6F (0.02 molar equivalent) and 15 parts by weight of bisphenol F epoxy resin (0.09 molar equivalent) were mixed, heated to 150° C. and reacted for 3 hours to form A6F binder resin.
[0045] Synthesis Example 2-4
[0046] 15 parts by weight of BAT monomer (0.03 molar equivalent), 15 parts by weight of bisphenol F epoxy resin (0.09 molar equivalent), and 30 parts by weight of HDGE (0.13 molar equivalent) were mixed, heated to 150° C. and reacted for 2 hours to form a BAT binder resin.
[0047] Synthesis Example 2-5
[0048] 15 parts by weight of monomer ABP (0.02 molar equivalent), 50 parts by weight of glycidyl methacrylate (0.35 molar equivalent, Glycidyl methacrylate, GMA), and 0.02 parts by weight of catalyst triphenylphosphate (Triphenylphosphate, TPP) were mixed, heated to 130° C. and reacted for 4 hours to form ABP acrylate epoxy binder resin.
[0049] Synthesis Example 2-6
[0050] 80.75 parts by weight of bisphenol F epoxy resin (0.475 molar equivalent), 35.52 parts by weight of acrylic acid (0.45 molar equivalent, Acrylic acid, AA), 0.291 parts by weight of catalyst TPP, and 0.078 parts by weight of thermal inhibitor hydroquinone monomethyl ether (MEHQ) were mixed, heated to 110° C. and reacted for 5 hours to form an acrylic ester binder resin.
[0051] Synthesis example 2-7
[0052] 15 parts by weight of monomer ABP (0.02 molar equivalent) and 30 parts by weight of hydrogenated bisphenol A epoxy resin (0.136 molar equivalent) were mixed and heated to 150° C. for reaction, but the reaction resulted in gelation and could not be used in subsequent applications.
[0053] Example 1
[0054] 5 g of ABP binder resin (first oligomer), 30 g of acrylate binder resin (Synthesis Example 2-6) (second oligomer), 1.88 g of dipentaerythritol penta- / hexa-acrylate (DPHA), 5.33 g of talc as inorganic filler, 0.65 g of free radical photoinitiator IRGACURE 819 (Phenylbis(2,4,6-trimethyl benzoyl)phosphineoxide), 0.7 g of free radical thermal initiator benzoyl peroxide (BPO), and 0.87 g of thermal curing agent 2-phenyl imidazole (2PZ) were mixed and ground at room temperature and stirred for degassing. The temperature of the instrument was then controlled at 25°C using a Brookfield Viscometers spindle, and the viscosity was measured at a speed of 1.0 rpm. The viscosity was about 250,000 cps. The above composition was coated on a glass substrate with a thickness of about 50 μm and the coating was heated at 365 nm and 1,500 mJ / cm 2 The coating was irradiated with ultraviolet light and then placed in a 120°C oven for curing for 30 minutes. The transmittance at 355 nm was then measured using an Agilent 8453 Spectrophotometer UV / VIS instrument.
[0055] The above resin composition was applied around the ITO glass substrate using a dispenser and then bonded to another ITO glass substrate. 2The laminated test piece was exposed to ultraviolet light and then placed in a 120°C oven for 30 minutes to form a frame glue to bond the two ITO glasses. Then, a double-column tensile tester (QC Teck) was used to measure the tensile shear strength to test the adhesion of the frame glue. The tensile rate was 20mm / min. Then, a KYO Nano DPSS DotBeam Type LLO was used to apply 355nm and 70μJ / cm per Hz. 2 The laser (external power: 50kHz) is used to apply the frame glue to perform the glue peeling test and calculate the peeling rate.
[0056] Example 2
[0057] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 20g of ABP binder resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 450,000 cps.
[0058] Example 3
[0059] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 5g of ODT binder resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 380,000 cps.
[0060] Example 4
[0061] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 10g of A6F binder resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 350,000 cps.
[0062] Example 5
[0063] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 5g of BAT binder resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 280,000 cps.
[0064] Example 6
[0065] Similar to Example 1, the difference is that 5g of ABP adhesive resin is replaced by 15g of ABP acrylate epoxy adhesive resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 350,000 cps.
[0066] Example 7
[0067] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by a combination of 5g of ABP binder resin and 15g of ABP acrylate epoxy binder resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as in Example 1, and the viscosity is about 300,000 cps.
[0068] Example 8
[0069] Similar to Example 1, the difference is that 5g of ABP binder resin is changed to 22g of ABP binder resin, and 1.88g of dipentaerythritol penta- / hexa-acrylate (DPHA) is changed to 2.88g. The rest of the composition of the resin composition and the property measurement of the sealant are the same as in Example 1, and the viscosity is about 300,000 cps.
[0070] Comparative Example 1
[0071] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 5g of bisphenol F epoxy resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 200,000 cps.
[0072] Comparative Example 2
[0073] Similar to Example 1, the difference is that 5g of ABP binder resin is replaced by 15g of bisphenol F epoxy resin. The rest of the composition of the resin composition and the property measurement of the sealant are the same as those of Example 1, and the viscosity is about 120,000 cps.
[0074] Table 1
[0075]
[0076] It can be seen from the examples and comparative examples that since the composition for forming the sealant disclosed in the present invention has an epoxy binder with a specific structure, it has acceptable adhesion before laser irradiation and has a high peeling ratio after laser irradiation.
[0077] Although the present disclosure has been disclosed as above with several preferred embodiments, they are not intended to limit the present disclosure. Any person with ordinary knowledge in the technical field can make any changes and modifications without departing from the spirit and scope of the present disclosure. Therefore, the scope of protection of the present disclosure shall be determined by the scope of the attached patent application.
Claims
1. A packaging structure, comprising: Photoelectric devices; as well as Frame glue, around the edge of the optoelectronic device, The frame glue is hardened by a composition, and the composition includes: a first oligomer; a second oligomer formed by reacting an acrylic group-containing compound with a liquid aromatic epoxy resin; Polyacrylate-based compounds; initiator; and Hardener, The first oligomer is formed by reacting a bis-acid monomer with (a) epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is: Where X is -O-, And R 1 Each is CH3 or CF3. 2 . The package structure as claimed in claim 1 , wherein the optoelectronic device comprises a liquid crystal display, a quantum dot light emitting diode display, an organic light emitting diode display, or a solar cell.
3. A method for disassembling a packaging structure, comprising: A packaging structure is provided, wherein the packaging structure comprises: Optoelectronic devices; and A frame glue surrounding the edge of the photovoltaic device; and The frame glue is irradiated with a laser to decompose the frame glue and disassemble the packaging structure, wherein the frame glue is hardened by a composition, and the composition includes: a first oligomer; A second oligomer formed by reacting an acrylic acid-containing compound with a liquid aromatic epoxy resin; a multi-acrylate compound; initiator; and Hardener, The first oligomer is formed by reacting a bis-acid monomer with (a) epoxy resin or (b) glycidyl methacrylate, wherein the structure of the bis-acid monomer is: Where X is -O-, And R 1 Each is CH3 or CF3.
Citation Information
Patent Citations
Epoxy resin solution
CN113396173A
Thermosetting resin composition
US4603180A